Development of Human Monoclonal Antibodies With Broad Reactivity for Rabies Postexposure Prophylaxis. - Wu, Meng; Peng, Xinyu; Xu, Weidi; Zhang, Hao; Fang, Lian; Liu, Xueqin; Miao, Faming; Liu, Quan; Mi, Shijiang; Xiao, Yuewen; Yu, Xinglong; Tu, Changchun; et al. (Journal of Medical Virology, 2024)
Rabies is an acute lethal disease causing by the neurotropic virus rabies virus (RABV). Rabies immune globulin (RIG) as an indispensable component of rabies postexposure prophylaxis (PEP) always faces with great challenges in terms of costs, stability and safety. Our objective is to develop a novel and potential fully human monoclonal antibodies (mAbs) cocktail for the improvement of rabies PEP. The neutralizing fully human mAbs were screened by using fully humanized antibody mice (CAMouseHG). Then, two mAbs 26-12 G and 5-7 G were selected with potential neutralizing activity to RABV by using fluorescent antibody virus neutralization test (FAVN), which specifically bind to antigenic sites I and III of RABV-glycoprotein (RABV-G), the key amino acid residues were further identified in position 336, 337 of 5-7 G and 226, 227, 228 of 26-12 G by using cross-linking and mass-spectrometry. Both mAbs are highly conserved across 8 RABV strains (distributing in 3 lineages: Asian, Cosmopolitan and Arctic-related) and 1 IRKV strain, and showed high neutralizing potential. Moreover, the in vivo experiment demonstrated that our cocktail can protect Kunming mice from a lethal RABV challenge. Collectively, we generate two noncompeting fully human mAbs (26-12 G, 5-7 G) and obtained cocktail CAM001 with their mixture. The high-potency and broad-spectrum neutralization of the cocktail supports its utility in human rabies PEP as an efficacious and affordable alternative to RIG products, particularly in endemic areas.